2016
DOI: 10.1167/iovs.15-18660
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ocular Levels of MicroRNA-148a in Cases of Retinal Detachment Promote Epithelial–Mesenchymal Transition

Abstract: Citation: Takayama K, Kaneko H, Hwang S-J, et al. Increased ocular levels of microRNA-148a in cases of retinal detachment promote epithelialmesenchymal transition. Invest Ophthalmol Vis Sci. 2016;57:269957: -270557: . DOI:10.1167 PURPOSE. The purpose of this study was to determine microRNA expression in vitreous and subretinal fluid (SRF) samples from patients with retinal detachment (RD). The pathological importance of the identified microRNA transcript levels was analyzed in vitro.METHODS. Vitreous fluid wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 39 publications
(42 reference statements)
0
31
0
Order By: Relevance
“…Lambrou et al . performed an animal experiment to examine the effect of SO or SOF on retinal pigment epithelial (RPE) cells that are thought to be one of the major players in inducing PVR by biologically promoting epithelial-mesenchymal transition 18, 19 . They suggested that vitreous cavity SO had an increased mitogenic activity for RPE cells compared to gas-filled or fluid-filled-vitreous 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lambrou et al . performed an animal experiment to examine the effect of SO or SOF on retinal pigment epithelial (RPE) cells that are thought to be one of the major players in inducing PVR by biologically promoting epithelial-mesenchymal transition 18, 19 . They suggested that vitreous cavity SO had an increased mitogenic activity for RPE cells compared to gas-filled or fluid-filled-vitreous 19 .…”
Section: Discussionmentioning
confidence: 99%
“…All vitreous samples were collected by dry vitrectomy at the beginning of vitrectomy surgery using a vitrectomy cutter before infusion initiation 18 . All samples were immediately stored at −80 °C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 lists the previous publications of studies that have analyzed microRNAs from surgically collected human vitreous. 4449 In most studies, microRNAs were detected by microRNA arrays, followed by reconfirmation by quantitative real-time polymerase chain reaction assay. Almost all of the current surgical instruments used in vitrectomy surgery are disposable and RNase-free, and collecting the vitreous from patients without any additional risks is possible during the regular surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…5052 Recently, aberrant expression of microRNAs in RPE cells undergoing EMT was reported. 47,49,5359 RPE cells undergo EMT and contribute to the pathogenesis of PVR. We focused on previous studies that have examined the effect of microRNAs on human RPE cells via EMT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation